2000
DOI: 10.1024/0300-9831.70.6.305
|View full text |Cite
|
Sign up to set email alerts
|

beta-Carotene, Retinol and alpha-Tocopherol Status in Calves Fed the First Colostrum at 0–2, 6-7, 12-13 or 24-25 Hours after Birth

Abstract: Effects on beta-carotene, retinol and alpha-tocopherol status of feeding 1st colostrum at 0-2, 6-7, 12-13 and 24-25 h after birth were studied in calves. beta-carotene, retinol and alpha-tocopherol concentrations decreased in colostrum during the first 2.5 d of lactation. Plasma beta-carotene, retinol and alpha-tocopherol concentrations in newborn calves were very low. Plasma beta-carotene concentrations increased up to d 3 after the 1st meal and during the 1st month were higher in calves fed 1st colostrum at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 0 publications
9
41
0
1
Order By: Relevance
“…In contrast to concentrations in plasma, vitamin A concentrations were markedly elevated in colostrum. This indicates an active transfer of vitamin A from plasma into colostrum, but in contrast to calves (Blum et al., 1997; Zanker et al., 2000; Puvogel et al., 2008) colostrum uptake was not followed by a clear increase in vitamin A concentrations in plasma of foals.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to concentrations in plasma, vitamin A concentrations were markedly elevated in colostrum. This indicates an active transfer of vitamin A from plasma into colostrum, but in contrast to calves (Blum et al., 1997; Zanker et al., 2000; Puvogel et al., 2008) colostrum uptake was not followed by a clear increase in vitamin A concentrations in plasma of foals.…”
Section: Discussionmentioning
confidence: 76%
“…Based on our studies, after intake of colostrum there is a rise of blood plasma concentrations of IgG 1 , Lf, total protein, albumin, essential amino acids and an impressive decrease of the glutamine/glutamate ratio. Plasma urea concentrations increase if high amounts of colostrum are fed and plasma glucose concentrations increase with a delay of several days; additionally there is a rise of plasma lipids (triglycerides, phospholipids‐lipids, total cholesterol and essential fatty acids) and of β ‐carotene, vitamins A and E. On the other hand, there are no marked or immediate changes of minerals or plasma concentrations of creatinine, lactate and nitrate (Ronge and Blum, 1988; Blum et al., 1997,2001; Hadorn et al., 1997; Hadorn and Blum, 1997; Egli and Blum, 1998; Hammon and Blum, 1998b, 1999; Hammon et al., 2000, 2002; Kühne et al., 2000; Zanker et al., 2000a,b, 2001a,b; Nussbaum et al., 2002; Schiessler et al., 2002; Muri et al., 2005). Because many other substances, especially proteins and peptides (Michanek and Ventorp, 1989) besides IgG 1 are absorbed intestinally and appear in the circulation (as shown for Lf even in the cerebrospinal fluid of neonatal calves) (Harada and Takeuchi, 2002; Talkuder et al., 2003), functional effects can be expected.…”
Section: Components Of Colostrummentioning
confidence: 99%
“…Intake of colostrum within the first 12 h after birth is important for normal plasma concentrations of β ‐carotene and vitamins A and E (Blum et al., 1997; Zanker et al., 2000b). If cows were fed vitamin A supplements during the dry period, plasma retinol concentrations in their colostrum and in plasma of their calves were increased up to 30 days p.n.…”
Section: Components Of Colostrummentioning
confidence: 99%
See 1 more Smart Citation
“…(1997)observed an increase in the α‐tocopherol concentration of colostrum from 5.3 to 7.5–10.49 mg/g of milk upon supplementation of vitamin E at 700–4000 IU/day to dry cows. Zanker et al. (2000) reported that delaying first colostrum intake by more than 12–13 h after birth impaired plasma α‐tocopherol status during the first month of life.…”
Section: Discussionmentioning
confidence: 99%